Tempered film and preparation method thereof
By adding copper sulfur quantum dots to the OCA optical rubber layer, polymer layer and silicone layer of the tempered film, the problem of lacking of the existing tempered membrane eye protection has been solved, and the higher blue light absorption rate and eye protection are achieved. Effect.
Patent Information
- Application Number
- CN202310927035.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-01-28
AI Technical Summary
The existing tempered film has poor eye protection function, which limits its promotion and application.
The tempered glass layer, OCA optical rubber layer, polymer layer, and silicone layer are used in sequence of stacked. Improve Blu -ray absorption and eye protection effects.
By increasing copper sulfur quantum dots, the tempered film can effectively absorb harmful blue light, slow down myopia, and have good compatibility with each functional layer, stable existence, and enhance the eye protection effect.
Smart Images

Figure CN119371901A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of tempered films, and in particular, to a tempered film and a preparation method thereof. Background Art
[0002] In the prior art, the current tempered film has the problem of poor eye protection function, which limits the promotion and application of tempered film. Summary of the invention
[0003] The purpose of the present application is to provide a tempered film and a preparation method thereof, which can improve the problem of poor eye protection function of the tempered film.
[0004] The embodiment of the present application is implemented as follows:
[0005] In a first aspect, an embodiment of the present application provides a tempered film, comprising a tempered glass layer, an OCA optical adhesive layer, a polymer layer and a silicone layer stacked in sequence, and at least one layer among the OCA optical adhesive layer, the polymer layer and the silicone layer is a target layer, and the target layer contains copper indium gallium sulfide quantum dots.
[0006] In the above technical solution, at least one layer of the OCA optical adhesive layer, the polymer layer and the silicone layer contains copper indium gallium sulfide quantum dots. Since copper indium gallium sulfide quantum dots have the ability to absorb harmful blue light and emit red light (their band gap width is narrow, and the corresponding fluorescence emission range is concentrated in the near-infrared region), they can effectively prevent and alleviate myopia, thereby making the corresponding tempered film have better eye protection effect; in addition, copper indium gallium sulfide quantum dots can also achieve good system compatibility with the inherent components in each functional layer, so that they can stably exist in each functional layer.
[0007] In some optional embodiments, in the target layer, the mass percentage of the copper indium gallium sulfide quantum dots is 0.1% to 5%.
[0008] Optionally, the mass percentage of copper indium gallium sulfide quantum dots is 0.5% to 1%.
[0009] In the above technical scheme, the mass proportion of copper indium gallium sulfide quantum dots in the target layer is limited to a specific range (if the mass proportion is too low, the corresponding blue light absorption rate is too low, and effective eye protection cannot be achieved; if the mass proportion is too high, that is, the content of inherent components in the functional layer is too low, the basic physical and chemical properties of the functional layer will not meet the requirements). While taking into account the basic physical and chemical properties of the tempered film (such as structural strength, transmittance, etc.), the corresponding tempered film can have a higher blue light absorption rate, thereby providing better eye protection effect.
[0010] Furthermore, limiting the mass proportion of the copper indium gallium sulfide quantum dots in the target layer to a more preferred range can better balance the basic physical and chemical properties (such as light transmittance) and eye protection effect of the tempered film.
[0011] In some optional embodiments, at least one of the following conditions A to D is met:
[0012] The thickness of the A tempered glass layer is 15 to 150 μm.
[0013] The thickness of the B OCA optical adhesive layer is 15 to 150 μm.
[0014] The thickness of the C polymer layer is 15 to 150 μm.
[0015] The thickness of the D silicone layer is 3 to 150 μm.
[0016] In the above technical solution, the thicknesses of the tempered glass layer, OCA optical adhesive layer, polymer layer and silicone layer are respectively limited within specific ranges, which can make the corresponding tempered film have a more suitable thickness on the one hand, and can make the corresponding tempered film have a more suitable transparency and blue light absorption rate on the other hand.
[0017] In some optional embodiments, at least one of the following conditions E to H is met:
[0018] The thickness of the E tempered glass layer is 60 to 100 μm.
[0019] The thickness of the F OCA optical adhesive layer is 60 to 100 μm.
[0020] The thickness of the G polymer layer is 60 to 100 μm.
[0021] The thickness of the H silica gel layer is 50 to 100 μm.
[0022] In the above technical solution, the thicknesses of the tempered glass layer, OCA optical adhesive layer, polymer layer and silicone layer are respectively limited within a more preferred range, which can make the corresponding tempered film have a more suitable thickness on the one hand, and on the other hand, make the corresponding tempered film have a more suitable transparency and blue light absorption rate.
[0023] In some optional embodiments, the particle size of the copper indium gallium sulfide quantum dots is 1 to 10 nm.
[0024] Optionally, the particle size of the copper indium gallium sulfide quantum is 5 to 10 nm.
[0025] In the above technical solution, the particle size of the copper indium gallium sulfide quantum dots is limited to a specific range because the quantum dots in this size range can be better dispersed in each functional layer. At the same time, the quantum dots of this size have a more suitable blue light absorption rate.
[0026] Furthermore, the particle size of the copper indium gallium sulfide quantum dots is limited to a more preferred range because the quantum dots in this size range can be better dispersed in each functional layer, and at the same time, the quantum dots of this size have a more suitable blue light absorption rate.
[0027] In some optional embodiments, the light transmittance of the OCA optical adhesive layer and / or the silicone layer is not less than 90%.
[0028] In the above technical solution, the light transmittances of the OCA optical adhesive layer and the silicone layer are respectively limited within specific ranges, so that the corresponding tempered film can have a more suitable light transmittance.
[0029] In some optional embodiments, the material of the polymer layer includes one or more of polycarbonate, polymethyl methacrylate, polyvinylidene fluoride, ethylene-vinyl alcohol copolymer, acrylonitrile-butadiene-styrene copolymer, polyvinylidene chloride, polyethylene terephthalate and polyethylene terephthalate.
[0030] The technical solution provided in the embodiments of the present application is applicable to polymer layers of the above-mentioned various materials, and can provide more feasible implementation plans, thereby facilitating the promotion and application of the technical solution of the present application.
[0031] In some optional embodiments, a release film layer is further provided on at least one side surface of the tempered film in the direction of stacking distribution.
[0032] In the above technical solution, the tempered film is added with a release film layer, which can effectively protect the internal structure of the tempered film, thereby reducing the risk of scratches on the internal functional layer. At the same time, it can also ensure the cleanliness of the bonding surface of the tempered film before the tempered film is bonded to the device.
[0033] In some optional embodiments, the release film layer is a PE release film, a PET release film, an OPP release film, a PC release film, a PS release film, a PMMA release film, a BOPP release film or a PVC release film;
[0034] Optionally, the thickness of the release film layer is 10-40 μm.
[0035] The technical solution provided in the embodiments of the present application is applicable to the release film layers of the above-mentioned various systems, and can provide more feasible implementation plans, thereby facilitating the promotion and application of the technical solution of the present application.
[0036] Furthermore, limiting the thickness of the release film layer within a specific range can better protect the internal structure of the tempered film.
[0037] In a second aspect, an embodiment of the present application provides a method for preparing a tempered film, comprising the following steps:
[0038] A tempered glass layer, an OCA optical adhesive layer, a polymer layer and a silicone layer are prepared, and copper indium gallium sulfide quantum dots are added to the raw materials for preparing at least one of the OCA optical adhesive layer, the polymer layer and the silicone layer to make it a target layer.
[0039] In the above technical solution, by preparing according to the above process, a tempered film with good eye protection effect can be prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 A schematic diagram of the structure of the first tempered film provided in an embodiment of the present application;
[0042] Figure 2 A schematic diagram of the structure of a second tempered film provided in an embodiment of the present application;
[0043] Figure 3 The blue light absorption performance test results of the target layer provided in the embodiment of the present application;
[0044] Figure 4 The light conversion performance test results of the target layer provided in the embodiments of the present application.
[0045] Icon: 10-tempered film; 100-tempered glass layer; 200-OCA optical adhesive layer; 300-polymer layer; 400-silicone layer; 500-release film layer. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.
[0047] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0048] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0049] In the prior art, current tempered films are mostly simple combinations of conventional functional layers. This form of tempered film can only meet basic physical and chemical performance requirements, such as the strength, light transmittance and thickness requirements of the tempered film, and usually cannot meet the corresponding eye protection needs.
[0050] Copper indium gallium sulfide (CuInGaS2) quantum dots have gradually replaced traditional II-VI quantum dots to become a new generation of fluorescent nanomaterials due to their advantages such as high absorption coefficient, stable fluorescence performance, low biological toxicity and large Stokes shift, and have attracted widespread attention in many fields such as biology and physics. In addition, due to the narrow band gap width of copper indium gallium sulfide quantum dots, their corresponding fluorescence emission range is concentrated in the near-infrared region, which just meets the purpose of red eye protection. At the same time, copper indium gallium sulfide system quantum dots also have the advantage of being Cd-free. Therefore, applying copper indium gallium sulfide (CuInGaS2) quantum dots to the field of tempered film technology can effectively improve the eye protection effect of tempered film.
[0051] The following is a detailed description of a tempered film and a preparation method thereof provided in an embodiment of the present application.
[0052] See also Figure 1 In the first aspect, an embodiment of the present application provides a tempered film 10, comprising a tempered glass layer 100, an OCA optical adhesive layer 200, a polymer layer 300 and a silicone layer 400 stacked in sequence, and at least one layer among the OCA optical adhesive layer 200, the polymer layer 300 and the silicone layer 400 is a target layer, and the target layer contains copper indium gallium sulfide quantum dots.
[0053] It should be noted that “at least one of the OCA optical adhesive layer 200, the polymer layer 300 and the silicone layer 400 is the target layer” may mean that only one of the layers contains copper indium gallium sulfide quantum dots, two of the layers contain copper indium gallium sulfide quantum dots, or all three layers contain copper indium gallium sulfide quantum dots.
[0054] It should be noted that when the tempered film 10 is used, the silicone layer 400 is used to bond to the screen of a device (eg, a mobile phone, a tablet, etc.).
[0055] It should be noted that the polymer layer 300 is disposed between the OCA optical adhesive layer 200 and the silicone layer 400 mainly to provide appropriate structural strength.
[0056] In the present application, at least one of the OCA optical adhesive layer 200, the polymer layer 300 and the silicone layer 400 contains copper indium gallium sulfide quantum dots. Since the copper indium gallium sulfide quantum dots have the ability to absorb harmful blue light and emit red light (their band gap width is narrow, and the corresponding fluorescence emission range is concentrated in the near-infrared region), they can effectively prevent and alleviate myopia, thereby making the corresponding tempered film 10 have a better eye protection effect; in addition, the copper indium gallium sulfide quantum dots can also achieve good system compatibility with the inherent components in each functional layer, so that they can stably exist in each functional layer.
[0057] It can be understood that the blue light absorption rate of the target layer is related to the mass ratio of the CIGS quantum dots in the target layer.
[0058] As an example, in the target layer, the mass proportion of copper indium gallium sulfide quantum dots is 1‰ to 5%, for example, but not limited to, the mass proportion of any one of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4% and 5%, or a range between any two of them.
[0059] In this embodiment, the mass proportion of copper indium gallium sulfide quantum dots in the target layer is limited to a specific range (if the mass proportion is too low, the corresponding blue light absorption rate is too low, and effective eye protection cannot be achieved; if the mass proportion is too high, that is, the content of inherent components in the functional layer is too low, the basic physical and chemical properties of the functional layer will not meet the requirements). The corresponding tempered film 10 can have a higher blue light absorption rate while taking into account the basic physical and chemical properties of the tempered film 10 (such as structural strength, transmittance, etc.), thereby providing better eye protection effect.
[0060] As an example, in the target layer, the mass proportion of copper indium gallium sulfide quantum dots is 0.5% to 1%, for example but not limited to any one of 0.5%, 0.6%, 0.7%, 0.8%, 0.9% and 1% or a range between any two of them.
[0061] In this embodiment, the mass proportion of the copper indium gallium sulfide quantum dots in the target layer is further limited to a more preferred range, which can better take into account the basic physical and chemical properties and eye protection effect of the tempered film 10.
[0062] It is understandable that the physical and chemical properties and blue light absorption rate of the tempered film 10 are related to the thickness of each functional layer.
[0063] As an example, at least one of the following conditions A to D is satisfied:
[0064] The thickness of the tempered glass layer 100 is 15 to 150 μm, for example but not limited to any one of 15 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm and 150 μm, or a range between any two of the values.
[0065] The thickness of the BOCA optical adhesive layer 200 is 15-150 μm, for example but not limited to any one of 15 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm and 150 μm, or a range between any two of the values.
[0066] The thickness of the C polymer layer 300 is 15 to 150 μm, for example but not limited to the thickness of any point value among 15 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm and 150 μm, or a range value between any two of them.
[0067] The thickness of D silicone layer 400 is 3 to 150 μm, for example but not limited to the thickness of any point value among 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm and 150 μm, or a range value between any two of them.
[0068] In this embodiment, the thicknesses of the tempered glass layer 100, the OCA optical adhesive layer 200, the polymer layer 300 and the silicone layer 400 are respectively limited within specific ranges, which can enable the corresponding tempered film 10 to have a more suitable thickness on the one hand, and enable the corresponding tempered film 10 to have a more suitable transparency and blue light absorption rate on the other hand.
[0069] As an example, at least one of the following conditions E to H is satisfied:
[0070] The thickness of the E-tempered glass layer 100 is 60-100 μm, for example but not limited to any one of 60 μm, 70 μm, 80 μm, 90 μm and 100 μm, or a range between any two of the values.
[0071] The thickness of the F OCA optical adhesive layer 200 is 60-100 μm, for example but not limited to any one of 60 μm, 70 μm, 80 μm, 90 μm and 100 μm, or a range between any two of the values.
[0072] The thickness of the G polymer layer 300 is 60-100 μm, for example but not limited to any one of 60 μm, 70 μm, 80 μm, 90 μm and 100 μm, or a range between any two thereof.
[0073] The thickness of the H silicone layer 400 is 50-100 μm, for example but not limited to any one of 50 μm, 60 μm, 70 μm, 80 μm, 90 μm and 100 μm or a range between any two of the values.
[0074] In this embodiment, the thicknesses of the tempered glass layer 100, the OCA optical adhesive layer 200, the polymer layer 300 and the silicone layer 400 are respectively limited within a more preferred range, which can enable the corresponding tempered film 10 to have a more suitable thickness on the one hand, and enable the corresponding tempered film 10 to have a more suitable transparency and blue light absorption rate on the other hand.
[0075] It can be understood that the blue light absorption rate of the CIGS quantum dots and the dispersion effect in the target layer are related to the size of the CIGS quantum dots.
[0076] As an example, the particle size of the copper indium gallium sulfide quantum dots is 1 to 10 nm, for example but not limited to any one of 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm and 10 nm, or a range between any two of them.
[0077] The form of the copper indium gallium sulfide quantum dots is not limited, and can be in the form of individual copper indium gallium sulfide quantum dot particles or in the form of copper indium gallium sulfide quantum dot polymer particles (i.e., a copper indium gallium sulfide quantum dot polymer prepared by dispersing copper indium gallium sulfide quantum dots in a polymer matrix).
[0078] In this embodiment, the particle size of the copper indium gallium sulfide quantum dots is limited to a specific range because the quantum dots in this size range can be better dispersed in each functional layer. At the same time, the quantum dots of this size have a more suitable blue light absorption rate.
[0079] As an example, the particle size of the CIGS quantum dots is 5 to 10 nm, for example but not limited to any point value among 5 nm, 6 nm, 7 nm, 8 nm, 9 nm and 10 nm, or a range value between any two of them.
[0080] In this embodiment, the particle size of the copper indium gallium sulfide quantum dots is further limited to a more preferred range because the quantum dots in this size range can be better dispersed in each functional layer, and at the same time, the quantum dots of this size have a more suitable blue light absorption rate.
[0081] It is understandable that the light transmittance of the tempered film 10 is related to the light transmittance of the OCA optical adhesive layer 200 and the silicone layer 400 .
[0082] As an example, the transmittance of the OCA optical adhesive layer 200 and / or the silicone layer 400 is not less than 90%. For example, the transmittance can be any point value among 90%, 91%, 92%, 93%, 94%, 95% and 96%, or a range value between any two of them.
[0083] In this embodiment, the light transmittances of the OCA optical adhesive layer 200 and the silicone layer 400 are respectively limited within specific ranges, so that the corresponding tempered film 10 can have a more suitable light transmittance.
[0084] It should be noted that the material of the polymer layer 300 is not limited.
[0085] As an example, the material of the polymer layer 300 includes one or more of polycarbonate, polymethyl methacrylate, polyvinylidene fluoride, ethylene-vinyl alcohol copolymer, acrylonitrile-butadiene-styrene copolymer, polyvinylidene chloride, polyethylene terephthalate and polyethylene terephthalate.
[0086] In this implementation, the technical solution provided in the embodiment of the present application is applicable to the polymer layer 300 of the above-mentioned various materials, and can provide more feasible implementation plans, thereby facilitating the promotion and application of the technical solution of the present application.
[0087] It is understandable that before using the tempered film 10 , if the functional layer of the tempered film 10 is directly exposed to the air, it is easy to cause contamination to the functional layer, thereby affecting the use of the tempered film 10 .
[0088] See also Figure 2 As an example, in the direction of stacking distribution, a release film layer 500 is also provided on at least one side of the tempered film 10 (i.e., a release film layer 500 is provided on the side of the tempered glass layer 100 and / or the silicone layer 400 away from the OCA optical adhesive layer 200).
[0089] It should be noted that when using the tempered film 10, it is only necessary to tear off the release film layer 500 and then bond the silicone layer 400 to the device.
[0090] In this embodiment, the tempered film 10 is additionally provided with a release film layer 500, which can effectively protect the internal structure of the tempered film 10, thereby reducing the risk of the internal functional layer being scratched. At the same time, it can also ensure the cleanliness of the bonding surface of the tempered film 10 before the tempered film 10 is bonded to the device.
[0091] It should be noted that the type of the release film layer 500 is not limited.
[0092] As an example, the release film layer 500 is a PE release film, a PET release film, an OPP release film, a PC release film, a PS release film, a PMMA release film, a BOPP release film or a PVC release film;
[0093] In this embodiment, the technical solution provided in the embodiment of the present application is applicable to the release film layer 500 of the above-mentioned various systems, and can provide more feasible implementation plans, thereby facilitating the promotion and application of the technical solution of the present application.
[0094] As an example, the thickness of the release film layer 500 is 10-40 μm, for example but not limited to any one of 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm and 40 μm or a range between any two of the thicknesses.
[0095] In this embodiment, the thickness of the release film layer 500 is limited within a specific range, which can better protect the internal structure of the tempered film 10 .
[0096] It should be noted that the forms of structures or units not specifically described or limited in the tempered film 10 are not limited and can be set according to conventional selections in the art.
[0097] In a second aspect, an embodiment of the present application provides a method for preparing a tempered film, comprising the following steps:
[0098] A tempered glass layer, an OCA optical adhesive layer, a polymer layer and a silicone layer are prepared, and copper indium gallium sulfide quantum dots are added to the raw materials for preparing at least one of the OCA optical adhesive layer, the polymer layer and the silicone layer to make it a target layer.
[0099] In the present application, a tempered film with good eye protection effect can be prepared according to the above process.
[0100] It should be noted that the specific preparation process of each functional layer is not limited and can be set according to the conventional selection in the art.
[0101] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0102] Example 1
[0103] An embodiment of the present application provides a tempered film, comprising a tempered glass layer, an OCA optical adhesive layer (QDL-SMJ), a polycarbonate polymer layer, a silicone layer and a PET release film layer which are stacked in sequence; wherein the OCA optical adhesive layer contains copper indium gallium sulfide quantum dots (CuInGaS2) with a mass percentage of 1% and a particle size of 5nm, and the thicknesses of the tempered glass layer, the OCA optical adhesive layer, the polycarbonate polymer layer, the silicone layer and the release film layer are 80μm, 90μm, 90μm, 70μm and 20μm, respectively.
[0104] Example 2
[0105] The embodiment of the present application provides a tempered film, which differs from Embodiment 1 in that the OCA optical adhesive layer contains 0.5% by weight of copper indium gallium sulfide quantum dots (CuInGaS2).
[0106] Example 3
[0107] The embodiment of the present application provides a tempered film, which differs from Embodiment 1 in that the OCA optical adhesive layer contains 5% by weight of copper indium gallium sulfide quantum dots (CuInGaS2).
[0108] Example 4
[0109] The embodiment of the present application provides a tempered film, which differs from Embodiment 1 in that the OCA optical adhesive layer contains 0.1% by weight of copper indium gallium sulfide quantum dots (CuInGaS2).
[0110] Comparative Example 1
[0111] The comparative example of the present application provides a tempered film, which differs from Example 1 in that the OCA optical adhesive layer does not contain copper indium gallium sulfide quantum dots (CuInGaS2).
[0112] Test Example 1
[0113] Blue light absorption rate test of target layer
[0114] Test method:
[0115] The test samples were configured according to the mass proportions of the copper indium gallium sulfide quantum dots in Examples 1 to 4 and Comparative Example 1, and then the blue light (wavelength of 380 to 530 nm) absorbance of each sample was tested using an infrared device. Then, the result of Comparative Example 1 was used as a control group to calculate the blue light absorbance corresponding to each embodiment, wherein the calculation formula of the blue light absorbance is as follows:
[0116]
[0117] Table 1 Blue light absorption rate test of each embodiment and comparative example
[0118] Sample name Quantum dot mass ratio (%) Blue light absorption rate (%) Light transmittance (%, 700nm) Example 1 1 38 95% Example 2 0.5 20 97% Example 3 5 56 85% Example 4 0.1 11 97% Comparative Example 1 0 0 98%
[0119] See Table 1 and Figure 3 (Wherein, curve A corresponds to Example 1, and curve B corresponds to Comparative Example 1). From the test results of Examples 1 to 4 and Comparative Example 1, it can be seen that the target layer containing copper indium gallium sulfide quantum dots can effectively absorb blue light compared to the target layer without copper indium gallium sulfide quantum dots.
[0120] From the test results of Examples 1 to 2 and Examples 3 to 4, it can be seen that when the mass percentage of quantum dots is controlled within the range of 0.5% to 1%, the target layer corresponding to the former can have both higher blue light absorption rate and light transmittance compared to when the mass percentage of quantum dots is not within this range.
[0121] Test Example 2
[0122] Photoconversion performance test of target layer
[0123] Test method:
[0124] The test samples were configured according to the mass proportion of the copper indium gallium sulfide quantum dots in Example 1 and Comparative Example 1, and then the fluorescence intensity of the samples at different wavelengths was tested using infrared equipment, wherein the test wavelength was 550-800 nm.
[0125] See also Figure 4 It can be seen (wherein curve A corresponds to Example 1, and curve B corresponds to comparative example 1), when copper indium gallium sulfide quantum dots are added to the target layer, compared with the case where no copper indium gallium sulfide quantum dots are added, the target layer corresponding to the former can emit red light with a wavelength of 650 to 690 nm, thereby stimulating the eyeball and playing a role in preventing and treating myopia.
[0126] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A tempered film, characterized in that: It comprises a tempered glass layer, an OCA optical adhesive layer, a polymer layer and a silicone layer which are stacked in sequence, and at least one of the OCA optical adhesive layer, the polymer layer and the silicone layer is a target layer, and the target layer contains copper indium gallium sulfide quantum dots.
2. The tempered film according to claim 1, characterized in that: In the target layer, the mass proportion of the copper indium gallium sulfide quantum dots is 0.1% to 5%; Optionally, the mass percentage of the copper indium gallium sulfide quantum dots is 0.5% to 1%.
3. The tempered film according to claim 1, characterized in that: Satisfy at least one of the following conditions A to D: A: The thickness of the tempered glass layer is 15 to 150 μm; B. The thickness of the OCA optical adhesive layer is 15 to 150 μm; C. The thickness of the polymer layer is 15 to 150 μm; D. The thickness of the silica gel layer is 3 to 150 μm.
4. The tempered film according to claim 3, characterized in that: Satisfy at least one of the following conditions E to H: E: The thickness of the tempered glass layer is 60-100 μm; F The thickness of the OCA optical adhesive layer is 60-100 μm; G The thickness of the polymer layer is 60 to 100 μm; The thickness of the silica gel layer is 50-100 μm.
5. The tempered film according to any one of claims 1 to 4, characterized in that: The particle size of the copper indium gallium sulfide quantum dots is 1 to 10 nm; Optionally, the particle size of the copper indium gallium sulfide quantum is 5 to 10 nm.
6. The tempered film according to any one of claims 1 to 4, characterized in that: The light transmittance of the OCA optical adhesive layer and / or the silicone layer is not less than 90%.
7. The tempered film according to any one of claims 1 to 4, characterized in that: The material of the polymer layer includes one or more of polycarbonate, polymethyl methacrylate, polyvinylidene fluoride, ethylene-vinyl alcohol copolymer, acrylonitrile-butadiene-styrene copolymer, polyvinylidene chloride, polyethylene terephthalate and polyethylene terephthalate.
8. The tempered film according to any one of claims 1 to 4, characterized in that: In the stacking distribution direction, a release film layer is further provided on at least one side surface of the tempered film.
9. The tempered film according to claim 8, characterized in that: The release film layer is a PE release film, a PET release film, an OPP release film, a PC release film, a PS release film, a PMMA release film, a BOPP release film or a PVC release film; Optionally, the release film layer has a thickness of 10 to 40 μm.
10. A method for preparing a tempered film according to any one of claims 1 to 9, characterized in that: The following steps are involved: The tempered glass layer, the OCA optical adhesive layer, the polymer layer and the silicone layer are prepared, and copper indium gallium sulfide quantum dots are added to the preparation raw materials of at least one of the OCA optical adhesive layer, the polymer layer and the silicone layer to make it a target layer.